An experience of workshop on introduction to statistical methods and SPSS hands-on training to enhance analytical skills among research professionals - Tellur, Laxmi; Sorganvi, Vijaya; Yadavannavar, M. C. (International Journal Of Community Medicine And Public Health, 2017)
Background: In a current scenario, research project and writing a thesis is one of the most important components of PG and Ph.D. studies and a potential area where the students are challenged by lack of structured guidance. Thus the workshop on “Introduction to Statistical Methods & ‘SPSS’ Hands-on Training” was conducted with the objectives, to know the impact of workshop and to obtain suggestions for improvement. Methods: The workshop on “Introduction to Statistical Methods & ‘SPSS’ Hands-on Training” conducted during 7-9 November, 2016 by the Department of Community Medicine, Shri B. M. Patil Medical College, Hospital and Research Centre in collaboration with University of Manitoba, Canada. The effectiveness of the workshop was assessed by pre-and-post tests using Multiple-Choice Questions (MCQ). Analysis was done using paired t test and Wilcoxon signed rank test. Results: A total of thirty six participants attended the sessions. The overall participant opinion about the workshop was positive. Majority of the participants were female. Majority of the participants were in the age group of 30-35 years (33%), followed by 25-30 years (28%). Majority of participants were MBBS (31%), MD (28%), other degree faulty members (22%) and PhD (22%). The mean score in pre-and-post-test was 12.52±6.17 and 13.98±6.50 respectively (Range=2-27) and was found significant difference in the scores between pre-and-post-tests (p=0.002). Conclusions: The recommendations and suggestions given by workshop participants were to increase the duration of the workshop. Participants were satisfied with the teaching methodology in the workshops.